Association between Dental Anomalies and Orofacial Clefts: A Meta-analysis. (October 2021) - Marzouk, T.; Alves, I.L.; Wong, C.L.; DeLucia, L.; McKinney, C.M.; Pendleton, C.; Howe, B.J.; Marazita, M.L.; Peter, T.K.; Kopycka-Kedzierawski, D.T.; Morrison, C.S.; Malmstrom, H.; et al.
Objectives: To conduct a systematic review and meta-analysis to assess whether individuals with nonsyndromic orofacial clefts (OCs) display a higher frequency of dental anomalies (DAs) when compared with individuals without OCs. Methods: A literature search of indexed databases (PubMed, Cochrane, Web of Science, Embase, Scopus, and LILACS) was conducted without language restriction up to and including February 1, 2020. Cross-referencing was used to further identify articles. Several cleft teams across the United States and Europe were contacted to obtain unpublished data. The eligibility criteria were observational studies with original data that statistically compared individuals with OC without syndromes and those without OC on any type of DA in primary and/or permanent dentition. Random effects meta-analysis through the Mantel-Haenszel estimator was used to evaluate the association between OC and DA based on odds ratios (ORs) with 95% confidence intervals (CIs). Results: The literature search generated 933 records, and 75 full-text articles were reviewed. Twenty-six studies encompassing 15, 213 individuals met the inclusion criteria. The meta-analysis revealed statistically significant associations between OC and agenesis (OR, 14.2; 95% CI, 9.4 to 21.3), supernumerary teeth (OR, 5.7; 95% CI, 3.3 to 9.7), developmental enamel defects (OR, 5.6; 95% CI, 3.5 to 9.0), microdontia (OR, 14.8; 95% CI, 4.0 to 54.6), peg-shaped anterior teeth (OR, 12.2; 95% CI, 3.6 to 41.2), taurodontism (OR, 1.7; 95% CI, 1.0 to 2.7), tooth malposition and/or transposition (OR, 5.6; 95% CI, 2.8 to 11.5), tooth rotation (OR, 3.2; 95% CI, 1.3 to 8.2), and tooth impaction (OR, 3.6; 95% CI, 1.1 to 12.2). The OR estimates of the reviewed studies exhibited significant heterogeneity ( P < 0.0001). No association was observed between OC and fusion and/or gemination. Conclusion: Within the limitations of this study, the available evidence suggests that individuals with OCs are more likely to present with a range of DAs than their unaffected peers. Knowledge Transfer Statement: The findings of the current review suggest that individuals with orofacial clefts (OCs) are more likely to present with a range of dental anomalies than their unaffected peers. Understanding the association between OCs and dental anomalies is essential in guiding clinicians during treatment-planning procedures and is important in raising our awareness of the possible need for future dental treatment for patients with OCs.